2018
DOI: 10.1097/scs.0000000000004603
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socioeconomic Factors on the Epidemiology of Maxillofacial Fractures in Southern Italy

Abstract: Maxillofacial fractures represent a serious public health problem. Their epidemiology is extremely variable and its analysis is crucial to establish effective treatment and prevention of these injuries. The aim of this multicentric retrospective study was to analyze causes, demographics, incidence, characteristics of 987 patients diagnosed with maxillofacial trauma between 2011 and 2015 at Complex Operative Unit of Maxillofacial Surgery of Federico II University of Naples and Magna Graecia University of Catanz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
2
24
0
2
Order By: Relevance
“…The main etiology for craniomaxillofacial fractures over the reported 6-year period was road traffic accidents (69.7%); this finding is supported by several studies where traffic accidents were the most prevalent etiology of facial trauma (Samieirad et al 2015). The second etiology was fall then followed by interpersonal violence which was the third responsible etiological cause; this result is similar to Sbordone et al 2018. Alternatively, other recent metacentric retrospective studies from Southern Italy in 2018 reported that the vast majority of cases were due to violent assaults followed by road traffic accident (RTA) then falls (Khan and Arif 2005).…”
Section: Discussionsupporting
confidence: 72%
“…The main etiology for craniomaxillofacial fractures over the reported 6-year period was road traffic accidents (69.7%); this finding is supported by several studies where traffic accidents were the most prevalent etiology of facial trauma (Samieirad et al 2015). The second etiology was fall then followed by interpersonal violence which was the third responsible etiological cause; this result is similar to Sbordone et al 2018. Alternatively, other recent metacentric retrospective studies from Southern Italy in 2018 reported that the vast majority of cases were due to violent assaults followed by road traffic accident (RTA) then falls (Khan and Arif 2005).…”
Section: Discussionsupporting
confidence: 72%
“…If implemented, the telemedicine platform will bring a variety of potential benefits for both patients and healthcare organizations [ 3 , 19 ]. In the field of maxillofacial surgery, it will be possible to think of a wider use as in the traumatology which, as is known, does not represent an emergency condition but a deferrable urgency [ 20 ]. Through a telematics meeting of a multidisciplinary team, it is possible to plan the treatment, through the visualization of the radiological images, and program the surgical intervention to minimize the duration of the hospital stay beyond that health spending.…”
Section: Discussionmentioning
confidence: 99%
“…In Victoria, Australia, while RTA was found to be the most common cause of MFF in a study on data obtained from 2001 to 2004 [16], another retrospective study on cases managed at the Alfred Hospital, also in Victoria from 2009 to 2011, showed that assault was the most common mechanism of injury [31]. Another recent multicentric retrospective study from Southern Italy in 2018 showed that the most frequent cause of facial injuries was assault (30.4%), followed by RTA (27.2%), and falls (23.2%) [32]. In contrast to that, the study done by Bocchialini et al from Brescia, Italy, reported RTA as the main cause of MFF (20%), followed by assault (14.4%), and sports (14.1%) [12].…”
Section: Discussionmentioning
confidence: 99%